“Pemberdayaan Masyarakat melalui Apotek Hidup untuk Kesehatan Keluarga di Desa Kemirian Kecamatan Tamanan Kabupaten Bondowoso” - Nur Alifia Husna; Arfiqoh Hasni Andini; Adinda Dzikria Ramadania; Maulidatul Jannah; Syafira Qurrotul A'yun; Siskarul Munawaroh; Tsania Nurhaliza; Eva Wulandari; Leni Tri Ramadhani; Putri Nur Rohmayanti; Qorinatul Fawaiz; Zanuba Arifah Khofsof; RB. Achmad Maulana; Muhammad Wahyu Firmansyah; Abd.Fiqrial Akbar; Mukaffan Mukaffan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The community of Kemirian Village, Tamanan District, Bondowoso Regency still faces family health problems, particularly the low utilization of traditional medicinal plants. Most residents depend on chemical medicines, while home yards remain underutilized. Through the Community Service Program (KKN), the student team empowered the community by developing apotek hidup (family medicinal gardens) to improve knowledge, awareness, and independence in maintaining family health. The program was implemented through socialization, mentoring, and direct practice of planting medicinal plants in household yards.The aim of this activity was to increase residents’ understanding of the importance of medicinal plants, encourage productive use of home yards, and reduce dependence on chemical medicines. It also sought to foster community self-reliance in disease prevention, promote healthy lifestyles based on local resources, and create a greener and healthier environment.The method applied was Participatory Action Research (PAR), covering observation, problem identification, socialization, training, mentoring, and evaluation. The results showed that residents began cultivating ginger, turmeric, galangal, and lemongrass, processing them independently, and strengthening cooperation to support natural family health